Barbie in the 12 dancing princesses - Redbank, Tennant; Grimm, Jacob 1785-1863.; Grimm, Wilhelm 1786-1859.; Ruby, Cliff; Lesser, Elana (New York The Random House, Inc., 2006)
This version of the fairy tale features Princess Genevieve and her twelve sisters as they escape their strict cousin by dancing the night away in a magic world, returning only to save their father, the king.
"Reading with help"--Cover.
Keywords: Tales -- Germany; Barbie (Fictitious character); Princesses; Dance; Fairy tales; Folklore -- Germany